Analysis of Radio communication solutions in small and isolated communities under the IEEE 802.22 standard - Arroyo Arzubi, Alejandro (2013)
In recent years the use of wireless communications has increased significantly. Rural communities without cable network communication have found a solution in wireless technologies. Based on previous fieldwork, this paper analyzes software development of integration based technologies for communication equipment. It focuses on the feasibility of the IEEE 802.22 standard as a solution to the wireless problem.